A comparison of the performance of the 2019 European League Against Rheumatism/American College of Rheumatology criteria and the 2012 Systemic Lupus International Collaborating Clinics criteria with the 1997 American College of Rheumatology classification criteria for systemic lupus erythematous in new-onset Chinese patients. (May 2020) - Teng, Jialin; Ye, Junna; Zhou, Zhuochao; Lu, Cui; Chi, Huihui; Cheng, Xiaobing; Liu, Honglei; Su, Yutong; Shi, Hui; Sun, Yue; Yang, Chengde
Background: New criteria published by the European League Against Rheumatism (EULAR) and the American College of Rheumatology (ACR) use a point system that gives varying weight to each of 22 criteria. The aim of this study was to compare the performance of the 2019 EULAR/ACR criteria and the 2012 Systemic Lupus International Collaborating Clinics (SLICC) criteria with the 1997 ACR criteria in a Chinese cohort. Methods: A cross-sectional observation study of patients with a clinical diagnosis of SLE was performed. We collected 199 new-onset SLE patients and 175 control subjects. The data were retrospectively collected to establish the patients who fulfilled the 1997 ACR, 2012 SLICC and 2019 EULAR/ACR criteria. The sensitivity and specificity of the three classification criteria were compared using McNemar's test. Results: The sensitivity and specificity of the 2019 EULAR/ACR criteria were 96.5% and 90.3%, respectively. For the 2012 SLICC criteria, the sensitivity and specificity were 92.0% and 84.0%, respectively, while for the 1997 ACR criteria, these two values were 75.4% and 96.0%. Leucopaenia (62%), arthritis (54%) and autoimmune haemolysis (45%) were the most frequently observed clinical manifestations in the group that fulfilled the 2019 EULAR/ACR criteria. Fever was reported by 39% of participants. Conclusion: Compared with the 1997 ACR and 2012 SLICC criteria, the 2019 EULAR/ACR criteria performed best in terms of sensitivity but less well in terms of specificity in Chinese new-onset lupus patients.